Prevalence of malocclusions in children aged 3 to 5 years who were breastfed, bottle- fed or mixed - F. G., Ibarra Aguilera; C. A, Meléndez Wong; S., Favela Flores; D. M., López Trujillo; M. F, Hernández Quintero; J. A., Sánchez Ledesma (Revista de Ciencias Médicas Torreón, 2025)
Breastfeeding is the best source of nutrients for the newborn. Breastfeeding promotes correct craniofacial development since it promotes the exercise of the muscles of mastication, which favors the correction of mandibular pseudoretrognathism that babies present at birth. Objectives: To know the prevalence of malocclusion in children aged between 3 and 5 years who were fed with exclusive breastfeeding, artificial or mixed feeding. Materials and methods: This research was exploratory and descriptive. A total of 70 children of both sexes were examined. Surveys were applied to the mothers to collect data on the type and duration of breastfeeding received. The clinical examination data collection sheet was filled out to observe if they presented any type of malocclusion. Results: 51.4% of the children received exclusive breastfeeding, while 37.1% (n=36) were fed with mixed breastfeeding (n=26) and 11.4% (8) with a bottle. 51.3% (n=36) presented some malocclusion, the most common being deep bite 10% (n=7) and anterior cross bite 8.6%. (n=6). 17.1% (n=12) presented lower midline deviation. Conclusions: It is concluded that, the more time of exclusive breastfeeding, the lower the presence of malocclusions.